Engaging with the World: Students of Comparative Law Write for Wikipedia - Norman Witzleb (Legal Education Review)
The face of postgraduate legal research in Australia has changed considerably in recent years. Certainly the number of students undertaking postgraduate research degrees at Australian law schools has burgeoned. Research degree programs in law include Masters by research, PhDs and SJDs. The rise in the numbers of postgraduate research degree students, together with an expanding array of research projects and methodologies, has generated new challenges for the postgraduate scholar, their supervisors and faculties seeking to support such students. These challenges arise in three areas: the intellectual challenges of postgraduate research in law; the personal aspects of the postgraduate research experience; and the supervision process and relationship. This article examines each of these areas, and argues that law faculties, postgraduate research supervisors and students need to reflect on the nature of contemporary postgraduate legal research, the purpose of and rationale for undertaking a postgraduate research degree in law and the unique and multifaceted challenges that must be met in developing, supervising and successfully completing a postgraduate degree project. With the current or prospective postgraduate research student in mind, this article points to some modest suggestions for enhancing law students’ research degree experience.